Northern Ireland: Evaluation of the Bail Supervisión and Support Scheme (2006) - Statistics and Research Branch (My University, 2016)
In February 2005 Deloitte was appointed to carry out an evaluation of the Youth Justice Agency’s (YJA) Bail Supervision and Support (BSS) scheme by the Northern Ireland Office (NIO). The research was undertaken over a 13 month period and the evaluation relates to the three elements within the BSS scheme, namely: 1) The Bail Support and Supervision scheme; 2) The Intensive Bail Support scheme (Inside Out); and 3) The Remand Fostering scheme.